ECO-EFFICIENCY INDEX ANALYSIS OF REINFORCED CONCRETE RESIDENTIAL HOUSES FOR IMPLEMENTATION IN GREEN BUILDING DESIGN - ABDUL HAMID, MOHD SAMSUDIN (2021)
Sustainable reinforced concrete design has become an innovative approachininnovation for reinforced concrete structural system that promotes sustainabledevelopment.